Simulation models to optimise hydrogen fuelled engine performance - Mohamad Kamil, Mohammed (2011)
Hydrogen is a strong candidate as an alternative fuel and energy carrier which could address answers to environmental pollution, emissions and geo-political tensions. This thesis aims to develop modeling codes for rapid simulation and optimisation for hydrogen fuelled engines (H2ICE). A composition and property model is developed for calculating the composition and thermodynamic properties of the multi-components gases in the H2ICE. The framework of this model encapsulates all possible situations from gases that are modelled on a molecular level to gases that are modelled as fresh air with some residuals. A one-dimensional model for a port injection H2ICE is also developed. This model uses a single-zone approach and simulates the different physical phenomena in the intake, compression, combustion and expansion processes. Previous models for heat transfer and heat release are introduced for hydrogen applications after proposing suitable modifications and calibrating factors. In addition, computational models are developed to investigate and optimise injection characteristics in direct injection H2ICEs as well as common rail port injection fuelling system. Following this, a one dimensional model is developed for an engine with dual pure fuels and blended fuels. The considered fuels are hydrogen, gasoline, methane, gasoline-hydrogen blends and methane-hydrogen blends. These models have been calibrated and validated against experimental works and the findings of previous studies. The results have showed the accuracy of the composition and property code and that it is a very useful tool for H2ICE simulations. Less than 0.3% deviation has been noticed for the entire considered range of temperature and equivalence ratio ( ). In addition, the port injection code has highlighted that spark timing as a very important contributor among the different parameters and how an optimisation for these contributors can enhance the performance. A calibration factor of 2.183 has been proved to give accurate results for the new heat transfer correlation. Besides, the deviation in the results of the heat release model was 2.3% in the worst case. From the injection models, it was shown that optimizing the injection parameters, in particular injection timing, are very crucial factors for engine performance and proper operation for the feeding system. The performance of H2ICE in comparison with engines use other fuels was investigated using the dual fuel model. Hydrogen fuel showed its superiority in the lean conditions ( < 0.4). Furthermore, the penalty and benefits from hydrogen enrichment were clarified. It was shown that adding small controllable mass factions of hydrogen (< 10%) to gasoline enhances the burning velocity and combustion process in the low speed range. However, a small reduction in the output power (< 6%) was documented. Adding hydrogen to methane showed greater advantages due to the extremely low burning velocity of methane. It can be recognized that the developed simulation codes are powerful tools for the H2ICE community. With these models, experiments can be supplemented and supported by fast calculations.